That is, given a non-injective assigment of integers to a finite collection we can find two objects (with the second objects y preceding the first value
This reduces to showing the contrapositive, namely
(
x:
m, y:
x. f(x) = f(y))
Inj(
m;
; f)
(computationally, since there are only finitely many choices for
So assuming that
(1) | ![]() ![]() ![]() ![]() |
and employing the definition
Def Inj(A; B; f) == a1,a2:A. f(a1) = f(a2)
B
a1 = a2
our proof reduces to showing that if
(2) |
then
a1<a2 &
a2<a1
which each follow from assumptions (1) and (2).
QED
This is a lemma for a proof of the pigeon-hole principle
Thm* m,k:
, f:(
m
k). k<m
(
x,y:
m. x
y & f(x) = f(y))
About:
![]() | ![]() | ![]() | ![]() | ![]() | ![]() |
![]() | ![]() | ![]() | ![]() |
![]() |